Proteomic analysis of the Treponema pallidum subsp. pallidum SS14 strain: coverage and comparison with the Nichols strain proteome - Houston, Simon; Marshall, Steven; Gomez, Alloysius; Cameron, Caroline E. (Frontiers in Microbiology, 2024)
IntroductionStrains of the syphilis spirochete, Treponema pallidum ssp. pallidum, group into one of two deep-branching clades: the Nichols clade or the globally dominant Street Strain 14 (SS14) clade. To date, in-depth proteome-wide analyses have focused on Nichols clade strains.MethodsThe T. pallidum SS14 clade reference strain (SS14) proteome was characterized via protein detection and quantification analyses using mass spectrometry, and comparison was made to the Nichols clade reference strain (Nichols) proteome.ResultsApproximately two thirds of all proteins from T. pallidum SS14 were detected and quantitated, allowing confirmation of expression of 259 proteins for the first time in this strain, including 11 known/putative outer membrane proteins (OMPs). SS14 and Nichols proteome comparative analyses demonstrated similar protein expression/quantification profiles between the two strains, and showed that inter-strain amino acid sequence differences are located primarily within predicted surface-exposed regions in 16 known/putative OMPs.DiscussionThis study provides the first comparative analyses of the proteomes from the T. pallidum SS14 and Nichols strains. The findings inform syphilis vaccine design by confirming the expression of known/predicted OMP vaccine candidates in SS14 treponemes, and via the finding that most inter-strain variable residues found in OMPs are predicted to be located in surface-exposed, host-facing regions of these proteins.